Clinical Significance of miR-339-5p in Early Diagnosis and Predicting Pregnancy Outcome of Chinese Patients with Liver Injury in Pregnancy - Ying Wang; Lichao Yuan; Falong Hu; Huilan Yu; Qiaofang Yang; Xiujuan Zheng (IMR Press, 2024)
Background: Liver injury in pregnancy significantly impacts the physical and mental health of pregnant women, and finding a potential therapeutic target is crucial for early prediction and improving adverse pregnancy outcomes. This study aims to examine the relationship between miR-339-5p expression and early diagnosis and pregnancy outcomes in patients experiencing liver injury in pregnancy. Methods: A retrospective study of 63 patients with liver injury in pregnancy. The expression of miR-339-5p in plasma of patients with liver health and liver injury in pregnancy was detected using quantitative real-time polymerase chain reaction (qRT-PCR). The value of miR-339-5p in the diagnosis and pregnancy outcomes of patients with liver injury in pregnancy was evaluated by receiver operating characteristic (ROC) and Cox regression analysis. Results: The alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bile acids (TBA), total bilirubin (TBIL) levels and miR-339-5p expression of patients in the intrahepatic cholestasis of pregnancy (ICP), hemolysis, elevated liver enzymes, and low platelet count (HELLP) and acute fatty liver of pregnancy (AFLP) groups, respectively, were statistically significant compared with those in the healthy control (HC) group (p < 0.05). MiR-339-5p expression was significantly lower in patients with liver injury in pregnancy compared to healthy individuals. This difference could be used to distinguish between healthy individuals and those with liver injury in pregnancy (area under the curve (AUC) = 0.897, 95% confidence interval (95% CI) = 0.843-0.951). In addition, ALT (r = -0.686), AST (r = -0.699) and TBA (r = -0.706) were highly negatively correlated with miR-339-5p expression, respectively. MiR-339-5p can be used as a biomarker of liver injury in pregnancy to predict adverse pregnancy outcomes. Conclusions: MiR-339-5p could potentially be used as a potential molecular marker for early diagnosis of liver injury in pregnancy and the prediction of adverse pregnancy outcomes.